Emergence and evolutions: Introducing sign language sociolinguistics - and Kusters, Annelies; Lucas, Ceil (Journal of Sociolinguistics, 2022)
The sociolinguistics of sign languages parallels as well as complements the sociolinguistics of spoken languages. All of the key areas of sociolinguistics, such as multilingualism, language contact, variation, and language attitudes—are of immediate relevance to sign languages. At the same time, sign language researchers using a range of data sources and methods (e.g., sign language corpora, linguistic elicitation, and linguistic ethnography) have showed that the unique natures and features of sign languages allow us to look at all these areas from a different vantage point. First, deficit perspectives on deafness serve to sharply distinguish the reality of sign languages from that of spoken languages. The linguistic status of sign languages has been long contested, and certain forms of signing are still labeled “nonlanguage.” The delineation and differentiation of sign languages, and of sign languages from other signing practices (e.g., gesturing, home sign) has therefore been a key issue. Second, sign languages are used by both deaf and hearing people, in contexts where spoken/written languages, and increasingly also other sign languages are in use, leading to complex multimodal forms of sign–spoken, sign–written, and sign–sign language contact, and to hierarchical constellations of language attitudes and ideologies in relation to signed and spoken languages and variants.
Keywords: gesture; iconicity; language attitudes; language contact; multilingualism; sign language; variation